2002
DOI: 10.1207/153248302760179138
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome and Misattribution: A Self-Perception, Individual Differences Perspective

Abstract: Self-perception theory suggests that premenstrual syndrome (PMS) may arise from the misattribution of hormone-induced bodily changes. If so, individual differences in the role of bodily responses in emotional feelings, measured in a separate expression-manipulation procedure, should be related to susceptibility to PMS. In Study 1, women responsive to cues from their bodies showed significant mood changes, both negative and positive, with their cycle, over a 60 day span; whereas women relatively unresponsive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Just as Laird (1974) suggested that a person may infer their own happiness from an awareness that they are smiling, our participants seemed to experience enhanced mood because of their awareness that they felt time flying. This corroborates the empirical support for SPT supplied by Laird and his colleagues (Duclos & Laird, 2001;Laird & Bresler, 1992;Schnall et al, 2002) as well as by Sackett et al, 2010, and Note. R 2 = Proportion of outcome variable variance explained by predictors.…”
Section: Mean Immersion Scores Across Experimental Groupssupporting
confidence: 86%
See 1 more Smart Citation
“…Just as Laird (1974) suggested that a person may infer their own happiness from an awareness that they are smiling, our participants seemed to experience enhanced mood because of their awareness that they felt time flying. This corroborates the empirical support for SPT supplied by Laird and his colleagues (Duclos & Laird, 2001;Laird & Bresler, 1992;Schnall et al, 2002) as well as by Sackett et al, 2010, and Note. R 2 = Proportion of outcome variable variance explained by predictors.…”
Section: Mean Immersion Scores Across Experimental Groupssupporting
confidence: 86%
“…This finding was in line with both the James-Lange theory of emotions (James, 1884) and self-perception theory (SPT; Bem, 1972), which states that people may come to know their own emotional states by inferring them from observation of their own behavior. Over the course of decades, James Laird (Duclos & Laird, 2001;Laird, 1974;Laird & Bresler, 1992;Schnall, Abrahamson, & Laird, 2002) has repeatedly demonstrated that emotional experiences are contingent upon a subconscious awareness of expressive behaviors. For example, smiling or furrowing the brow seems to influence the degree to which an individual feels happy.…”
Section: We Also Have Fun When Time Fliesmentioning
confidence: 99%
“…Later investigations demonstrated that this individual difference may be tied to other self-perception processes as well. The same people whose emotional feelings were not impacted by facial expressions were also less likely to experience cognitive dissonance after performing a counterattitudinal behavior (Laird & Berglas, 1975), less likely to experience mood-congruent memories (Schnall & Laird, 2003), reported fewer symptoms of premenstrual syndrome (Schnall, Abrahamson, & Laird, 2002), and were more likely to overeat and become overweight or obese (McArthur, Solomon, & Jaffee, 1980). Similarly, only those who were accurate at perceiving their heart rate showed a positive correlation between heart rate and feelings of anxiety (Schandry, 2007).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Third, experiments investigating the influence of emotional states on judgment require that participants do not correctly attribute the induced feeling to its true source (e.g., Lapate, Rokers, Li, & Davidson, 2014;Schnall, Abrahamson, & Laird, 2002;Schwarz & Clore, 1983; for a review, see Schwarz, 2012). If one experiences disgust while considering a morally questionable action, the action is likely to seem disgusting and immoral (at least for people who are more attentive to bodily states).…”
mentioning
confidence: 99%